Dominance, libido and serving capacity of Garole rams under semi-arid region of Rajasthan - Maurya, V P; Mittal, J P; Naqvi, S M K; Joshi, A (The Indian Journal of Animal Sciences, 2012)
Behaviour studies were conducted on 12 adult rams of Garole breeds which were transported from hot humid climate of Sunderban area of West Bengal to semi-arid climate of Avikanagar in Rajasthan. The observations were recorded on their agnostic, investigatory, precopulatory, mounting and ejaculatory behaviour with a view to assess dominance, libido and serving capacity of these rams under semi-arid environment. The dominance rating of these rams were recorded on the basis of incidences of chasing, bunting and fights. The dominant rams had higher frequency and higher number of investigations of ewes. The incidence of anogential sniffing and frequency of bouts of leg kicking were also higher in dominant rams. The latency period, the number of mounts between ejaculations and time taken for first, second and third ejaculations were consistently lower in dominant rams.